The rationale for alternative fertilization: Equilibrium isotherm, kinetics and mass transfer analysis for urea-nitrogen adsorption from cow urine; Resource-Efficient Technologies; Vol. 1, Iss. 2 - Ganesapillai M. (2015, 2015)
Title screen